Counting the uncounted burdens: intimate partner violence in migrant communities - systematic review of the literature. (4th September 2019) - Daoud, Nour
This article provides a systematic review of the empirical evidence related to intimate partner violence (IPV) in migrant communities. The main goal of the article is to understand the exposure to and impact of IPV among migrant women, the drivers of IPV and the barriers to disclosure and help-seeking. The search resulted in 36 studies that meet the inclusion and quality assessment criteria. The findings show that migrant women are exposed to various levels of IPV in refugee and immigrant contexts. Following the ecological model, the drivers of IPV are categorised at the individual level (e.g., alcohol and substance abuse), the relationship/household level (e.g., reversal of gender roles), and the community/society level (e.g., social acceptability of IPV). The literature review also highlights gaps in the literature, such as the relationship between IPV and other types of violence suffered by women. The article has recommendations, one of which is to conduct future large-scale studies that consider the intersectional, and post-structural feminist perspectives.